2013
DOI: 10.1149/2.044312jes
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Copper Thin Films on Insulators Using Supercritical Fluid Deposition

Abstract: A one-step fabrication method for direct supercritical fluid deposition (SCFD) of Cu on insulators was developed. This overcomes the limitation of conventional SCFD, which cannot directly deposit Cu on insulators. In our one-step method, a relatively small amount of an Mn precursor was mixed with a Cu precursor to deposit a CuMn x O y composite layer on an insulative underlayer. This underlayer then acted as a buffer layer, allowing subsequent Cu deposition. This method successfully achieved Cu deposition on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…(12) Cabañas et al presented that a high reaction temperature was required for direct SCFD on an insulator. They also demonstrated Au SCFD on SiO 2 , (15) and CuMn x O y SCFD on SiO 2 was reported by Uejima et al (16) Although direct Cu SCFD on SiO 2 was also demonstrated, (17) a Cu film on SiO 2 has very poor adhesivity. (18) Inserting an adhesion layer can contribute to the improvement of adhesion on a SiO 2 surface.…”
Section: Introductionsupporting
confidence: 52%
“…(12) Cabañas et al presented that a high reaction temperature was required for direct SCFD on an insulator. They also demonstrated Au SCFD on SiO 2 , (15) and CuMn x O y SCFD on SiO 2 was reported by Uejima et al (16) Although direct Cu SCFD on SiO 2 was also demonstrated, (17) a Cu film on SiO 2 has very poor adhesivity. (18) Inserting an adhesion layer can contribute to the improvement of adhesion on a SiO 2 surface.…”
Section: Introductionsupporting
confidence: 52%